Concurrent multi-path data transfer using modified SCTP - (:unkn) unknown (IEEE Computer Society, 2013)
SCTP (Stream Control Transmission Protocol) has multi-homing features, but SCTP implementations do not actively use this feature. If the active path is disabled or packets are lost SCTP uses alternative paths; this multi-homing feature can be used to transfer data concurrently. In this study, data has been sent from these multi-homing paths and load balancing has been implemented on these paths, with the development of an adaptive algorithm for load balancing to transfer data via concurrent multi-path on low bandwidth networks. This algorithm enables data to be sent using all available paths in networks and thus leads to higher transfer rates. © 2013 IEEE.
Keywords: concurrent transfer; load balancing in SCTP; multi-homing; SCTP; transport protocols